Redesain Bioreaktor Guna Mempercepat Proses Fermentasi Pembuatan Pupuk Organik di Desa Minggirsari Kecamatan Kanigoro Kabupaten Blitar - Pratama, Novi Ariyan; Murnawan, Hery (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Alongside the increasing potential of the agriculture and plantation sectors in Minggirsari Village, Blitar Regency, there have been concerns among farmers regarding the decreasing supply of both subsidized and non-subsidized chemical fertilizers. However, these concerns were validated with the invention of an automatic anaerobic bioreactor by Nawang Sonia in 2023. The device is capable of reducing the fermentation process time from the initial 14-21 days to just 3-5 days. Although the designed device still had some functional limitations hindering its performance, a redesign was deemed necessary. The redesign was conducted using the Quality Function Deployment method through the distribution of questionnaires or Voice of Customer. Subsequently, a House of Quality was obtained, which served as the basic concept for the device's redesign. From this research, eight features were added to the device. The results showed that the device was more optimal, flexible, and effective than the previous anaerobic bioreactor design.